2020
DOI: 10.1186/s40623-020-01228-9
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-day variation of pre-reversal enhancement in the equatorial ionosphere based on GAIA model simulations

Abstract: Using a whole atmosphere–ionosphere coupled model GAIA (ground-to-topside model of atmosphere and ionosphere), we have investigated which parameters mainly control day-to-day variation of vertical plasma drift at the evening terminator over magnetic equator, so-called pre-reversal enhancement (PRE). Day-to-day variations of the peak PRE are compared with those of electron density, eastward current density and eastward neutral wind in the E- and F-region over Chumphon (10.7° N, 99.4° E; 0.86° N magnetic latitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…This correlation strength agrees with a recent study by Ghosh et al. (2020), which recorded a correlation coefficient of 0.4 at h'F over 300 km. The zonal wind velocity in the F‐region illustrated a positive correlation with EPB occurrences at the peak of PRE, hence, the F‐region winds can influence the peak PRE through the F‐region dynamo along with E and F region coupling mechanisms.…”
Section: Resultssupporting
confidence: 93%
“…This correlation strength agrees with a recent study by Ghosh et al. (2020), which recorded a correlation coefficient of 0.4 at h'F over 300 km. The zonal wind velocity in the F‐region illustrated a positive correlation with EPB occurrences at the peak of PRE, hence, the F‐region winds can influence the peak PRE through the F‐region dynamo along with E and F region coupling mechanisms.…”
Section: Resultssupporting
confidence: 93%
“…This study also emphasizes that the results presented in Figure 5 are strong observational evidence of the statistical relationship between the eastward neutral wind in the evening thermosphere and the PRE magnitude. Previous studies of the role of the eastward neutral wind on the PRE mechanism have employed models or numerical simulations (e.g., Eccles et al, 2015;Ghosh et al, 2020). In this study, wind data from the GOCE satellite has provided empirical evidence that stronger eastward neutral winds appear to generate larger PRE magnitudes.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Ghosh et al (2020) demonstrated the use of the GAIA model to examine the roles of the zonal neutral wind and the EEJ on the daily variation of the PRE magnitude in the Southeast Asian longitude sector and equinoctial months -the same region and seasons as the data analyzed in this study; thus our observa-tions invite comparison to the GAIA simulations, which found cross-correlation coefficients for the relationships between the wind and the PRE and between the EEJ and the PRE of approximately 0.5 and 0.4, respectively. These values support our observational conclusions that the wind and the EEJ act in a balanced manner in affecting the PRE magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…They were able to reproduce the day-to-day variability of PRE V Z with realistic amplitude (3-6 m/s in standard deviation) under geomagnetically quiet (Kp=0.33) and high solar-flux (F 10.7 =200) conditions, thus establishing the role of large-scale waves for the day-to-day variability of PRE. Ghosh et al (2020) also reported day-to-day variations of PRE reproduced by another whole atmosphere model, GAIA (Jin et al, 2011).…”
Section: Accepted Articlementioning
confidence: 86%